Lyriothemis lucifera spec. nov. from the Andaman Islands, India (Odonata: Libellulidae) - Seehausen, Malte; Dawn, Prosenjit (Zootaxa, 2024)
Lyriothemis lucifera spec. nov. (holotype ♂: 18.iv.1998, Long Island, Rangat county, North and Middle Andaman district, Andaman Islands, India, ex.-coll. M. Hämäläinen, Wen-Chi Yeh, RMNH.INS. 1152914; deposited at Naturalis Biodiversity Centre Leiden, the Netherlands), is described and figured. This new species belongs to the 3rd group of Lyriothemis Brauer, 1868. Photographs of the name-bearing specimens of Lyriothemis magnificata (Selys, 1878), Lyriothemis daui Krüger, 1902, and Lyriothemis laui Krüger, 1902 are provided.